2012
DOI: 10.4401/ag-6143
|View full text |Cite
|
Sign up to set email alerts
|

Ground effects induced by the 2012 seismic sequence in Emilia: implications for seismic hazard assessment in the Po Plain

Abstract: <p>Since May 16, 2012, a seismic sequence has affected a wide portion of the Emilia Region (northern Italy), chiefly for the Modena and Ferrara Provinces. The first mainshock (Ml 5.9; focal depth, ca. 6 km) occurred on May 20, 2012, with the epicenter located a few kilometers north of Finale Emilia. A second main shock (Ml 5.8; focal depth, ca. 10 km) occurred on May 29, 2012, about 12 km west of the first earthquake, with the epicenter near Medolla (Figure 1). The seismic sequence has been characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The 2012 earthquakes triggered a widespread interest on the seismic hazard assessment in the alluvial plain area of the Emilia-Romagna Region [Di Manna et al 2012, Malagnini et al 2012, Meletti et al 2012, Milana et al 2014, Papathanassiou et al 2015, Tonni et al 2015]. The available data on the subsurface were however scanty.…”
Section: Introductionmentioning
confidence: 99%
“…The 2012 earthquakes triggered a widespread interest on the seismic hazard assessment in the alluvial plain area of the Emilia-Romagna Region [Di Manna et al 2012, Malagnini et al 2012, Meletti et al 2012, Milana et al 2014, Papathanassiou et al 2015, Tonni et al 2015]. The available data on the subsurface were however scanty.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread liquefaction phenomena occurred during the 2012 seismic sequence of Ferrara (Di Manna et al, 2012) in a comparable stratigraphic and sedimentological context, which can be considered as a natural laboratory to investigate surface structures related to liquefaction. This seismic sequence was characterized by two main events that occurred during May 2012 (20 May 2012 Mw 6.1 and 29 May 2012 Mw 5.9), with a hypocentral depth of 6.3 km and 10.2 km, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the 2012 seismic sequence of Ferrara as a natural laboratory for directly testing parameters related to liquefaction, it was observed that liquefaction occurred only during the two main events (Di Manna et al, 2012). A maximum distance of 27 km from the epicenters was recorded for significant liquefaction, but no liquefaction occurred during the other events with a lower magnitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESI scale integrates the traditional macroseismic scales, of which it represents the evolution, allowing to assess the intensity parameter also where buildings are absent or damage-based diagnostics saturate. For this purpose, we revisit three representative case histories from very different tectonic environments: the reverse faulting of the 2012 Emilia sequence (May 20, M w = 5.8; and May 29, M w = 5.6; Di Manna et al, 2012) in the Po Plain foredeep environment of N Italy; the normal faulting of August 21, 2017 Casamicciola earthquake (M d = 4.0;Nappi et al, 2018) in the Ischia volcanic island, S Italy; and the devastating February 4, 1976, Guatemala earthquake (M = 7.5;Porfido et al, 2015), along the leftlateral Motagua Fault at the boundary between the N America and Caribbean plates.…”
Section: Local Indexes Based On a Nationwide Threshold For Rainfall-induced Landslidesmentioning
confidence: 99%